Power quality improvement of synchronous generators using an active power filter - Abu-Jalala, Al-Hussein Mohammed; Cox, Tom; Gerada, Christopher; Rashed, Mohamed; Hamiti, Tahar; Brown, Neil (IEEE, 2018)
Active power filters (APF) are used to improve power quality and are commonly connected in parallel with the load at the point of common coupling (PCC). They are used to compensate for harmonics from nonlinear loads, for reactive power compensation and/or balancing mains currents. This paper will investigate the effect of using an APF to improve the output power quality of a simplified synchronous generator (SSG) with distorted back-EMF. A Matlab Simulink model for the SSG is built to simulate all the system, the APF and the proposed generator. Using an APF, simulation and experimental results show significant improvements in generator output current and reduced the THD in the system.